Transformers for natural language processing : build, train, and fine-tune deep neural network architectures for NLP with Python, PyTorch, TensorFlow, Bert, and GPT-3 /: build, train, and fine-tune deep neural network architectures for NLP with Python, PyTorch, TensorFlow, Bert, and GPT-3. (2022) - Rothman, Denis
No abstract available